Where next for early years? Funding, affordability and the Budget. (2nd May 2023) - Cowley, Sue
Abstract : The cost of childcare is still a key concern for working parents and setting closures are on an upwards trajectory, as questions about the affordability and sustainability of the sector have featured widely in the press. Following the announcement of an extension to funding entitlements in the recent Budget, the sector looks set for a bumpy ride. Sue Cowley explores the latest picture.